Target controlled infusion of remifentanil for fetal analgesia and immobilization during the ex utero intrapartum treatment procedure for Congenital High Airway Obstruction (CHAOS) - Abdul Karim, Othman; Mohd Sayuti, Razali; Mohd Habibullah, Zakaria; Noraslawati, Razak; Ruwaida, Isa (2019)
The objective of this case report is to highlight the use of maternal Target Controlled Infusion (TCI) of Remifentanil to provide immobilization and analgesia to the fetal during Ex utero Intrapartum (EXIT) procedure. A 37 weeks of gestation fetal was diagnosed with Congenital High Airway Obstruction Syndrome (CHAOS). EXIT procedure was preferred as the most favourable approach of management. With the concurrent use of general anaesthesia, TCI Remifentanil was infused to the mother with the aim to provide fetal immobilization and analgesia during surgical tracheostomy on the fetal. Tracheostomy was successfully done with excellent fetal immobilization without the requirement of other medications or muscle relaxant administered to the fetal circulation. In performing a delicate fetal airway surgery, the anaesthesiologist must achieve loss of consciousness, adequate analgesia and more importantly immobility to the fetal with a significant uterine relaxation while safely anaesthetizing the mother. There are several approaches of achieving fetal analgesia and immobility during EXIT procedure. These include the direct administration of anaesthetic drugs to the fetal blood circulation via intravenous or intramuscular route, intra-amniotic delivery or delivery of the anaesthetic drugs directly through maternal blood circulation in addition to inhalational anaesthetic agents. In our case, fetal analgesia and immobility was achieved through maternal blood circulation using TCI of Remifentanil and coupled with inhalational agent of sevoflurane.